URGENSI HUKUM ISLAM DALAM PENYELESAIAN SENGKETA EKONOMI SYARI’AH - Nailur Rahmi (JURIS (Jurnal Ilmiah Syariah), 2018)
Implementation of Undang-Undang Nomor 3 Tahun 2006 about PerubahanUndang-undang Nomor 7 Tahun 1989 about Pengadilan Agama (Islamic Court)points out that Pengadilan Agama has authority to solve conflicts related to sharia economics. Chapter 50 points out that any problems among Moslems dealing with sharia economy should be solved in Pengadilan Agama. Due to the development of sharia economic activities, such as Sharia Banks, Sharia micro financial instutions, and many other, the possibility of legal problems are open. In solving such problems, beside referring to Undang-Undang and Kompilasi Hukum Ekonomi Syariah (Compilation of Sharia Economic Law), judges also consulted The Quran, the Sunnah and other resources for Islamic law, especially in relation to Fiqh Muamalah. By consulting those resources as considerations, any legal decision will lead to the invention of new law (rechtsvinding) which is based on law interpretation and construction. This is made possible since Pengadilan Agama has established law resources, especially about shariaeconomy, such as books of fiqh which is very contextual in application. It is expected that the decisions which have been made will be better in terms of quality and accountability.